A co-produced review of the experiences of Black male detention under mental health legislation: Challenging discrimination in psychiatry using The Silences Framework - Heyes, Kim; Brodrick, Isaiah; Best, Debbie; Thompson, Kenny; Leah, Caroline; Miller, Eula; Craig, Elaine; Serrant, Laura; Dixon, Jeremy; Bergqvist, Anna; Lantta, Tella; Sewell, Hári; et al. (Public Library of Science (PLoS), 2026)
The number of detentions under mental health legislation is growing, disproportionately impacting Black men. Previous research into the over-detention of Black people is repetitive and solutions to reduce disparities are ineffective, not enacted, or outdated. This review is original and novel in using a lived experience lens within the Silences framework, to interpret and validate review findings and make actionable recommendations to enable change, reduce Black men’s detention rates and improve experiences. The systematic review searched three databases: EBSCO, ProQuest, and PMC. Search terms included: ethnicity: Black African Caribbean; gender: male; and detention: detained under mental health legislation. Searches were conducted in September 2021 and February 2024 and included papers from 2000 to 2024. The review was conducted using the NIHR systematic review protocol. Searches resulted in 15,300 papers, which were reduced to 34 papers for inclusion in the thematic analysis. People with lived experience on the review team explored the Silences missing in the literature and co-developed the findings and recommendations. Three themes were developed and are presented as ‘Screaming Silences’ - a concept that amplifies what is known (by patients, family and friends, professionals, and others), but is not explicitly discussed within literature: (1) contextual identity; (2) culture, spirituality, and religion; and (3) power, language, and communication. People with lived experience discussed what these themes meant to them. Their views are key to flipping the narrative, and support change for Black men compulsorily detained in mental health settings. Findings show that academic understanding of the detrimental treatment and care of Black men has barely changed in twenty years. The recommendations centre on: patient involvement and clear communication; reducing disparities through anti-discriminatory policies and practice; the promotion of cultural competence; community campaigns, collaboration, and support for carers; monitoring and auditing; and improving future research through co-production.